Living Ihya and Harmonizing the Spiritual Essence: Sheikh Washil's Fiqh-Sufistic as the Bedrock of Spiritual-Based Islamic Law in Nusantara - Faiz, Muhammad Fauzinudin; Dakhoir, Ahmad; Ali, Zezen Zainul; Amal, M. Khusna (El-Mashlahah, 2024)
The harmonization of Islamic law through the spiritual dimension and the transformation of Islamic teachings in seems to be a disconnect between the spiritual essence of Islam and its legal framework in contemporary times. This disconnect raises questions about the extent to which current Islamic law fully embraces the spiritual principles that have become an integral part of the Nusantara heritage. Therefore, this research aimed to explore how Sheikh Washil's fiqh-sufistic can function as an Islamic legal framework, based on the spiritual principles of the Nusantara and answer contemporary issues. This research used an interdisciplinary approach with two approaches, History and Islamic Law. This research explored the literature of Sheikh Washil including his contribution to Islamic law. The findings of this study: first, fiqh-sufistic contributes to spiritual studies within a legal framework in order to understand and practice the characteristics of Islam Nusantara with an inclusive approach through the values of living ihya in da'wah and thought. Second, fiqh-sufistic presents a balanced approach to Islamic law, which is in harmony with the cultural context and heritage. The integration of fiqh-tasawuf shows the harmonization of Islamic law and the transformation of Islamic teachings in the context of the Nusantara. Third, the prevalence of fiqh-sufistic has had a transformative impact on the inclusive religious landscape, encouraging a deeper understanding of Islam as a way of life, not just a set of legal rules.